(untitled) (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2026)
Brangkal Printing, as one of the SMEs in the printing services sector, still faces marketing challenges because its promotional efforts tend to be conventional, its use of social media is not yet optimal, and the management’s ability to create and manage digital content remains limited. These conditions have prevented the company’s marketing reach and customer engagement from reaching their full potential. This community service activity aims to enhance the partner’s capacity in implementing digital marketing through the optimization of social media. Implementation methods include observation and identification of the partner’s needs, digital marketing training, guidance on social media management, hands-on digital content creation, and evaluation via pre-tests, post-tests, questionnaires, and interviews. The results of the activity show an increase in the partners’ understanding and skills in managing social media accounts, creating more engaging promotional content, and responding to customers more quickly and in a structured manner. The average post-test score showed an increase compared to the pre-test, indicating an improvement in participants’ competencies after completing the program. Additionally, the partners now have more active social media accounts, a promotional content calendar, and the ability to independently operate digital marketing features. The tangible contributions of this initiative include enhanced human resource capacity in digital marketing, expanded promotional reach, and the establishment of a sustainable social media-based marketing system to support the improved competitiveness of Brangkal Printing SMEs.